2018
DOI: 10.5847/wjem.j.1920-8642.2018.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous fluid selection rationales in acute clinical management

Abstract: 0.9% sodium chloride was mostly chosen. The choice of IVF was mainly based on departmental practice. Adequacy of guideline, information and training, and time for revision on IVF prescription were average, indicating significant training deficit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Finally, compared with the treatment in septic shock, the infused volume of normal saline was much lower in our study subjects, which might have weakened the association between normal saline infusion and chloride fluctuation. Although other balanced crystalloid fluid such Plasma-Lyte (Na, 140 mmol/L; Cl, 98 mmol/L) has been reported to cause less hyperchloremia ( 21 ), normal saline remains to be the first choice in most clinical scenarios ( 22 ). The encouraging findings from two recent trials that lactated Ringer's solution or Plasma-Lyte A reduced hospital death or adverse kidney events in contrast to saline in critically ill ( 23 ) and non-critically ill ( 24 ) adult patients may have the potential to change current practice.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, compared with the treatment in septic shock, the infused volume of normal saline was much lower in our study subjects, which might have weakened the association between normal saline infusion and chloride fluctuation. Although other balanced crystalloid fluid such Plasma-Lyte (Na, 140 mmol/L; Cl, 98 mmol/L) has been reported to cause less hyperchloremia ( 21 ), normal saline remains to be the first choice in most clinical scenarios ( 22 ). The encouraging findings from two recent trials that lactated Ringer's solution or Plasma-Lyte A reduced hospital death or adverse kidney events in contrast to saline in critically ill ( 23 ) and non-critically ill ( 24 ) adult patients may have the potential to change current practice.…”
Section: Discussionmentioning
confidence: 99%
“…Not surprisingly, therefore, static measures have proven unable to accurately determine fluid responsiveness. [5][6][7][8][9][10][11][12] A metaanalysis of 23 research studies demonstrated that invasive monitoring of CVP was not only a poor predictor of fluid responsiveness, but also conferred numerous risks including infection and mechanical complications. [6] The measurement of pulmonary artery occlusion pressure requires the placement of a pulmonary artery catheter; this device is also associated with increased morbidity and mortality.…”
Section: Traditional Assessment Of Fl Uid Responsivenessmentioning
confidence: 99%